Disrupting Sleep: The Effects of Sleep Loss on Psychotic Experiences Tested in an Experimental Study With Mediation Analysis. (4th August 2017) - Reeve, Sarah; Emsley, Richard; Sheaves, Bryony; Freeman, Daniel
Abstract: Our view is that insomnia may be a causal factor in the occurrence of psychotic experiences such as paranoia and hallucinations. However, the causal relationship is not established. The aim of the study was to investigate the causal role of insomnia in psychotic experiences via a sleep restriction manipulation. The study was a within-subjects crossover design that included a planned mediation analysis. Sixty-eight nonclinical volunteers underwent a sleep loss condition (restricted to 4 h sleep for 3 nights) and a control condition (standard sleep) in randomized order in 2 consecutive weeks, with a weekend washout period. Psychotic experiences (paranoia, hallucinations, grandiosity, and cognitive disorganization) and candidate mediating variables (negative affect and related processes, working memory, decision making, and perceptual processing) were assessed before and after each condition. Actigraphy verified an average sleep duration of 5 h 15 min in the sleep loss condition, vs 6 h 58 min in the control condition. After the sleep loss condition, relative to the control condition, participants reported significant increases in paranoia, hallucinations, and cognitive disorganization, with no significant changes in grandiosity. The sleep loss condition was also associated with significant increases in negative affect, negative self and other cognitions, worry, and working memory impairment. Mediation analyses indicated that changes in psychotic experiences were mediated by changes in negative affect and related processes, but not memory impairment. The overall conclusion is that insomnia has a causal role in the occurrence of certain psychotic experiences, and that a key route is via negative affect.